Why high comparative advantage does not guarantee market growth in Indonesian cocoa butter exports? - Manalu, Doni Sahat Tua; Putri, Chintya Eka; Gandhi, Prima (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2026)
Indonesia ranks as the world's third-largest cocoa butter exporter, contributing 11% to global exports. However, export values have declined from USD 791 million (2020) to USD 627 million (2023), presenting a paradox given Indonesia's substantial production capacity, established infrastructure, and supportive policy interventions.This study analyzes the comparative advantage and export performance dynamics of Indonesian cocoa butter in global markets during 2010–2023, using an integrated Revealed Comparative Advantage (RCA) and Export Product Dynamics (EPD) framework. Time-series export data were obtained from UN COMTRADE, ITC, and Trademap for HS code 180400. The study compares Indonesia with Malaysia across two contrasting destination markets: the United States (mature, high-value market) and Estonia (emerging EU gateway). RCA analysis measures comparative advantage based on export structure specialization, while EPD categorizes competitive positioning into four quadrants: Rising Star, Falling Star, Lost Opportunity, and Retreat. Indonesia demonstrates exceptionally high RCA values (Estonia: 87.80; US: 50.43), confirming strong comparative advantage. However, EPD analysis reveals divergent market dynamics: Indonesia achieves Rising Star status in Estonia (expanding market share in growing market) but Falling Star status in the US (gaining share in declining market). Malaysia falls into the Lost Opportunity quadrant in both markets, indicating declining competitiveness. The findings reveal a critical RCA-EPD paradox: high comparative advantage does not guarantee sustainable market growth. While RCA reflects structural export specialization, EPD captures dynamic competitive positioning. This divergence underscores that export strategies must integrate both static comparative advantage and dynamic market responsiveness. For Indonesia, maintaining competitiveness requires market diversification, product upgrading, and adaptive strategies tailored to market-specific demand trajectories.